Treatment Patterns and Clinical Outcomes Among Patients with Metastatic Non-small Cell Lung Cancer Without Actionable Genomic Alterations Previously Treated with Platinum-Based Chemotherapy and Immunotherapy - Jerome H. Goldschmidt; Wan-Yu Tseng; Yunfei Wang; Janet Espirito; Anupama Vasudevan; Michelle Silver; Jackie Kwong; Ruchit Shah; Elizabeth Marrett (Adis, Springer Healthcare, 2024)
Abstract Background For patients with metastatic non-small cell lung cancer, timely molecular testing is essential to determine the appropriate course of therapy. Initial treatment with platinum chemotherapy and/or an immune checkpoint inhibitor (ICI) is the standard of care for patients without actionable genomic alterations. Objective We aimed to assess treatment patterns and clinical outcomes among patients with metastatic non-small cell lung cancer, no actionable genomic alterations, and with prior ICI and platinum-based chemotherapy in a community oncology setting. Methods This retrospective observational study examined electronic health records from adult patients with an initial metastatic non-small cell lung cancer diagnosis without actionable genomic alterations from 2017 to 2019. Patients had received a subsequent line of therapy (LOT) [index] after discontinuing platinum-based chemotherapy plus an ICI in the previous one or two LOTs. Patient demographics and clinical characteristics were analyzed descriptively. Clinical outcomes were evaluated using Kaplan-Meier analyses. Results Among the study population (n = 961), the most common index LOT regimens were non-platinum-based chemotherapies (57.3%), platinum-based chemotherapies (12.9%), ICI-based chemotherapies (12.7%), platinum + ICI-based chemotherapies (9.4%), and other (7.7%). The most common post-index LOT regimens were non-platinum based (61.2%), ICI based (15.3%), platinum based (10.7%), platinum + ICI based (3.2%), and other (2.5%). Median time to treatment discontinuation, time to next treatment, and overall survival were numerically longest with index LOT ICI-based regimens (6.5, 9.9, and 18.9 months, respectively) and shortest with platinum-based regimens (2.8, 5.3, and 8.0 months, respectively) and non-platinum-based regimens (2.6, 5.0, and 7.8 months, respectively). Conclusions Among patients with metastatic non-small cell lung cancer without actionable genomic alterations previously treated with platinum + ICIs, non-platinum chemotherapy agents were most commonly prescribed in the index LOT. Clinical outcomes including time to treatment discontinuation, time to next treatment, and overall survival were short, highlighting the unmet need for more effective later-line treatments.